2022
DOI: 10.2147/ijgm.s355435
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Potential Predictor of Biochemical Recurrence in Prostate Cancer

Abstract: Background Prostate cancer is a common malignancy in men. Radical prostatectomy is one of the primary treatment modalities for patients with prostate cancer. However, early identification of biochemical recurrence is a major challenge for post-radical prostatectomy surveillance. There is a lack of reliable predictors of biochemical recurrence. The purpose of this study was to explore potential biochemical recurrence indicators for prostate cancer. Materials and Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…The occurrence of BCR in patients with PCa after radical treatment indicates the likelihood of distant metastasis and the development of castration-resistant prostate cancer (CRPC) [ 8 ]. Although the advancement in salvage treatment regimens, including radiation therapy, androgen deprivation therapy, chemotherapy, and even intensive multimodal therapy, has improved the prognosis of patients with PCa, most still die within 2 to 4 years [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The occurrence of BCR in patients with PCa after radical treatment indicates the likelihood of distant metastasis and the development of castration-resistant prostate cancer (CRPC) [ 8 ]. Although the advancement in salvage treatment regimens, including radiation therapy, androgen deprivation therapy, chemotherapy, and even intensive multimodal therapy, has improved the prognosis of patients with PCa, most still die within 2 to 4 years [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Antonarakis et al reported that the median time for metastasis-free survival of patients with BCR was 10 years [ 7 ]. Studies have shown that clinicopathological factors, such as clinical staging, PSA, Gleason score, and surgical margin, cannot accurately predict BCR [ 8 ]. Therefore, it is urgent to seek new and more accurate BCR predictive markers and explore the pathogenesis of PCa.…”
Section: Introductionmentioning
confidence: 99%
“…The previous study has revealed that prostate cancer risk alleles are associated with prostate cancer volume and prostate size [ 63 ]. Downregulation of PAH and AOC1 and upregulation of DDC, LIN01436, and ORM1 were associated with the development of prostate cancer [ 8 , 64 ]. Molecular and cellular biological studies are also closely related to the site of prostate tumorigenesis [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Serum prostate-specific antigen (PSA) is the mainstay to detect the BCR of patients after surgery [ 6 ], and it has been recommended to keep close monitoring until PSA reaches 0.2 ng/mL [ 7 ]. In addition to PSA kinetics, Gleason score, PSA density, pathological and clinical stages, surgical margin, and other clinical factors have been studied for their prognostic significance, however, these factors could not predict BCR independently [ 8 ]. To better distinguish the recurrence risk and evaluate the prognosis after RP, more innovative predictors or models are unmet clinical needs.…”
Section: Introductionmentioning
confidence: 99%
“…However, more than one quarter of patients still experience biochemical recurrence (BCR) after surgery, which subsequently progresses to distant metastasis and PCa-related death [ 2 ]. Current predictions of PCa prognosis after curative intent are based on clinical and pathological features whose predictive efficacy remains unsatisfying [ 3 ]. Therefore, it is crucial to predict and confirm the BCR status of patients in time in order to classify and manage BCR patients with individualized treatment plans.…”
Section: Introductionmentioning
confidence: 99%